2017
DOI: 10.1631/jzus.b1600510
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and differentiation of myeloid-derived suppressor cells after fluid resuscitation in mice with hemorrhagic shock

Abstract: Abstract:Objective: To investigate the distribution and differentiation of myeloid-derived suppressor cells (MDSCs) in hemorrhagic shock mice, which are resuscitated with normal saline (NS), hypertonic saline (HTS), and hydroxyethyl starch (HES). Methods: BALB/c mice were randomly divided into control, NS, HTS, and HES resuscitation groups. Three subgroups (n=8) in each resuscitation group were marked as 2, 24, and 72 h. Flow cytometry was used to detect the MDSCs, monocytic MDSCs (M-MDSCs), and granulocytic/n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The major populations of MDSCs can be divided into two large groups: polymorphonuclear (PMN-MDSC) and monocytic (M-MDSC), which use different mechanisms to suppress immune responses ( 20 ). Our previous study demonstrated that MDSCs declined after hemorrhagic shock, but increased gradually after fluid resuscitation, and the ratio of M-MDSC to PMN-MDSC decreased after 24 h fluid resuscitation, but increased later ( 21 ). However, the distribution and differentiation of the subsets of MDSCs after sepsis are not well-known and few studies have demonstrated the expression of PD-L1 on MDSCs and the subsets during sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…The major populations of MDSCs can be divided into two large groups: polymorphonuclear (PMN-MDSC) and monocytic (M-MDSC), which use different mechanisms to suppress immune responses ( 20 ). Our previous study demonstrated that MDSCs declined after hemorrhagic shock, but increased gradually after fluid resuscitation, and the ratio of M-MDSC to PMN-MDSC decreased after 24 h fluid resuscitation, but increased later ( 21 ). However, the distribution and differentiation of the subsets of MDSCs after sepsis are not well-known and few studies have demonstrated the expression of PD-L1 on MDSCs and the subsets during sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these observations, the modulation of MDSC function by systemic steroids may represent a new therapeutic target, although detailed data on the timing of use and type of steroid are still lacking. Furthermore, the function of MDSC in sepsis and trauma has not been sufficiently studied [ 105 , 106 ]. The vast majority of data are based on studies in tumors, although an increasing number of studies highlight the role of MDSC subtypes in the resolution of inflammation after severe sepsis and trauma [ 106 , 107 ].…”
Section: Dehydroepiandrosterone (Dhea)mentioning
confidence: 99%
“…Lung injury may develop into acute respiratory distress syndrome (ARDS) and is one of the main causes of death of THS (4). Lung injury after THS is characterized by an excessive uncontrolled inflammatory response and vascular endothelial injury (5)(6)(7). Thus, the reduction of the pulmonary inflammatory response and vascular endothelial injury are important in improving the curative effect of THS.…”
Section: Introductionmentioning
confidence: 99%